2021
DOI: 10.1101/2021.02.11.430687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A compact spatial map in V2 visual cortex

Abstract: Vision plays a critical role in guiding spatial navigation. A traditional view of the visual cortex is to compute a world-centered map of visual space, and visual neurons exhibit diverse tunings to simple or complex visual features. The neural representation of spatio-visual map in the visual cortex is thought to be transformed from spatial modulation signals at the hippocampal-entorhinal system. Although visual thalamic and cortical neurons have been shown to be modulated by spatial signals during navigation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…Thus, the spatially-tuned neurons described here are intermixed with neurons that do not differ much in their response properties from neurons in the primary auditory cortex. This evidence provided here adds to other recent studies that described spatially tuned neurons in many structures outside the hippocampal system 50, 51 , including visual cortex 52 , somatosensory cortex 53 , retrosplenial cortex 54 , and premotor cortex 55 . The role of these neurons in auditory processing, as well as in spatial navigation, requires further study.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the spatially-tuned neurons described here are intermixed with neurons that do not differ much in their response properties from neurons in the primary auditory cortex. This evidence provided here adds to other recent studies that described spatially tuned neurons in many structures outside the hippocampal system 50, 51 , including visual cortex 52 , somatosensory cortex 53 , retrosplenial cortex 54 , and premotor cortex 55 . The role of these neurons in auditory processing, as well as in spatial navigation, requires further study.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, grid-like computation can be implemented in the somatosensory cortical columns to track the location of tactile features relative to the objects being touched. In the case of rat V2 grid cells, theory-driven hypotheses have been confirmed by preliminary experimental findings (Hawkins et al, 2019 ; Long et al, 2021a ). In the previous report, S1 grid cells were recorded across Layer IV-VI of the rat S1HL (hindlimb) area, and V2 grid cells were recorded across superficial and deep layers of the rat V2M area (Long and Zhang, 2021 ; Long et al, 2021a ); and some evidence has shown clustered or columnar structures in the primary and secondary areas of these sensory cortices (Horton and Adams, 2005 ; Laramee et al, 2013 ; Hubatz et al, 2020 ).…”
Section: From Perception To Cognitionmentioning
confidence: 75%
“…Notably, grid-like representations not only appear in the human mEC, but also in other traditionally thought non-spatial frontal brain areas, such as the human orbitofrontal cortex (OFC), ventromedial prefrontal cortex (vmPFC) and anterior and posterior cingulate cortex (ACC and PCC) (Constantinescu et al, 2016 ; Bao et al, 2019 ). Recently, grid cells have also been discovered in the rat primary somatosensory cortex (S1) (Long and Zhang, 2021 ) and the secondary visual cortex (V2) (Long et al, 2021a ). What are the roles and functional significance of these sensory cortical grid cells?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we only investigated the rodent hippocampal circuit in this study, our “place” decoding analysis and methods can be readily applied to other rodent neocortical areas that encode spatial information, such as the entorhinal cortex, retrosplenial cortex, parietal cortex, primary somatosensory cortex, and primary and secondary visual cortices ( Hafting et al, 2005 ; Whitlock et al, 2008 ; Mao et al, 2017 ; Ji and Wilson, 2007 ; Haggerty and Ji, 2015 ; Hu et al, 2018 ; Long and Zhang, 2021 ; Long et al, 2021 ). Moreover, it has been shown that these sensory “place cells” are also modulated with local cortical theta rhythms during run behaviors and preserved phase precession ( Long and Zhang, 2021 ; Long et al, 2021 ). To date, experimental evidence of spatial modulated responses across many neocortical areas beyond the traditional hippocampal formation has been accumulating.…”
Section: Discussionmentioning
confidence: 99%